Signposts for an Eastern Orthodox inclusive anthropological ethics - Maican, Petre (Scottish journal of theology, 2022)
Despite the strong interest of Eastern Orthodox theologians in the area of anthropology, their reflection has almost never included intellectual disability. The article aims to take the discussion further by providing the contours of an inclusive anthropological ethics. In this sense, it will develop constructively the three main principles of Dumitru Stăniloae's dialogical anthropology: (1) that each human being is a person because she is called to dialogue with God from the womb of her mother; (2) that this dialogue with God is mediated by one's neighbour; (3) that the materiality of creation is meant to be transformed into a gift of communion with other humans and God.